High Sample Throughput LED Reactor for Facile Characterization of the Quantum Yield Spectrum of Photochemically Produced Reactive Intermediates - Wu, Binbin; Liu, Tian; Wang, Yanling; Zhao, Guoqiang; Chen, Baoliang; Chu, Chiheng (Environmental science & technology, 2021)
Photochemically produced reactive intermediates (PPRIs) by natural photosensitizers such as chromophoric dissolved organic matter (CDOM) play numerous key roles in aquatic biogeochemical processes. PPRI productions rely on both the intensity and the spectrum of incident sunlight. While the impacts of sunlight intensity on PPRI productions are well-studied, there remains insufficient understanding of the spectrum-dependence of PPRI productions. Here we designed a high sample throughput reactor equipped with monochromatic LED lights for systematic assessments of wavelength-dependent productions of four important PPRI species, i.e., triplet-state excited CDOM (3CDOM*), singlet oxygen (1O2), hydrogen peroxide (H2O2), and hydroxyl radical (•OH), in CDOM solutions. The quantum yields of PPRIs followed the order: 3CDOM* > 1O2 ≫ H2O2 > •OH. Moreover, PPRI quantum yields decreased with the light wavelength increasing from 375 to 490 nm and sharply decreased to zero above 490 nm, while the shapes of quantum yield spectra differed among PPRI species. Simulations on PPRI productions under varying season, latitude, altitude, and cloud cover conditions show that the sunlight spectrum plays a role as equally important as intensity in determining PPRI productions and PPRI-mediated transformations of aquatic nutrients and micropollutants. Therefore, incorporating the spectrum dependence of PPRI productions will advance our understandings of PPRI-driven biogeochemical processes and pollutant dynamics under varying spatial-temporal and climatic conditions. Regarding this, the high sample throughput LED reactor sheds light on a new approach for the facile characterization of PPRI quantum yield spectrum.